THE EFFECT OF NAOH CATALYST RATIO ON MANUFACTURING BIODISEL FROM OFFGRADE CPO - Hartono, Rudi; Muklis, Muklis; Pamungkas, Wisnhu (World Chemical Engineering Journal, 2020)
Biodiesel is a type of alternative diesel fuel derived from plant oils or animal fats produced through the transesterification process. Previous biodiesel studies have stated that esterification reactions are carried out when the content of free fatty acids in vegetable oil raw materials is greater than 2%. If the content of free fatty acids is smaller than 2% then the process of transesterification reaction is carried out.                The research aims to find out the optimum operating conditions of biodiesel manufacturing with low grade CPO raw materials using the esterification and transesterification process. The research began with the analysis of low grade CPO raw materials, then carried out the esterification process with the H2SO4 catalyst and continued the transesterification process with NaOH catalyst. Fixed variables in the study were oil volume, 1% of H2SO4 catalyst, mole ratio of oil and methanol 1:6, reaction time and reaction temperature of 60 oC. The fixed variables in the study were NaOH catalyst ratios in the transesterification process of 0.5%, 1% and 1.5%. The oil obtained is analyzed the content of free fatty acids, density, viscosity, and water content.                The results of the study obtained the physical and chemical properties of low grade CPO, namely water content 0.042% and free fatty acids 49.03. Optimum operating conditions are obtained with a catalyst ratio of NaOH of 1% with a methyl ester yield of 60.80%. The resulting methyl ester has a viscosity value of 5,381 cSt, a density of 870 kg/m3, an acidic content of 0.11 and a water content of 0.028.